ANALISIS TATA RUANG KOLEKSI YANG OPTIMAL BAGI KENYAMANAN PEMUSTAKA DI PERPUSTAKAAN UNIVERSITAS PGRI PALEMBANG - Agustri, Yangyi; Bety, Bety (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Libraries are built to support the achievement of goals by providing collections or library materials to be utilized by students, lecturers, and library staff. Activities in this library are based on the PKL (Field Work Practice) program of the Library Science Study Program, Faculty of Adab and Humanities, Raden Fatah State Islamic University Palembang. This activity is intended so that library staff know how to organize the optimal space for the comfort and satisfaction of the library users, it is also expected that from this activity the library users can more easily find the information or library materials needed. In the implementation of the activity, the author used the interview method and direct observation to the library by directly observing the state of the library layout, this activity was assisted by other PKL students who were also grouped for PKL, and also assisted by one of the officers on duty there. Based on the results of direct research, on the 3rd floor is a circulation room, librarian workspace, reading room, and collection room. Then in the arrangement of the room on the 3rd floor is quite optimal where this library has paid attention to various factors of good and correct library room arrangement.